Climate change reduces the mitigation obtainable from sequestration in an Australian farming system. (4th September 2019) - Thamo, Tas; Addai, Donkor; Kragt, Marit E.; Kingwell, Ross S.; Pannell, David J.; Robertson, Michael J.
Abstract : Agricultural research on climate change generally follows two themes: (i) impact and adaptation or (ii) mitigation and emissions. Despite both being simultaneously relevant to future agricultural systems, the two are usually studied separately. By contrast, this study jointly compares the potential impacts of climate change and the effects of mitigation policy on farming systems in the central region of Western Australia's grainbelt, using the results of several biophysical models integrated into a whole‐farm bioeconomic model. In particular, we focus on the potential for interactions between climate impacts and mitigation activities. Results suggest that, in the study area, farm profitability is much more sensitive to changes in climate than to a mitigation policy involving a carbon price on agricultural emissions. Climate change reduces the profitability of agricultural production and, as a result, reduces the opportunity cost of reforesting land for carbon sequestration. Nonetheless, the financial attractiveness of reforestation does not necessarily improve because climate change also reduces tree growth and, therefore, the income from sequestration. Consequently, at least for the study area, climate change has the potential to reduce the amount of abatement obtainable from sequestration – a result potentially relevant to the debate about the desirability of sequestration as a mitigation option.